Linking human-disturbed landscapes with pathogen prevalence in wildlife: a meta-analysis - White, Alison, author; Antolin, Michael F., advisor; Ballweber, Lora R., committee member; Lockwood, Dale R., committee member (Colorado State University. Libraries, 2015)
The percentage of earth disturbed by humans is rapidly growing. In a review of the available literature in wildlife disease ecology we performed a meta-analysis to determine if human disturbed landscapes increased prevalence of pathogens and parasites, compared to undisturbed landscapes. We analyzed a total of 68 cases of host-pathogen and host-parasites reported in 34 publications. We carried out analyses at two levels: 1.) studies reporting prevalence values for both disturbed and undisturbed landscapes, of which 46 cases within 13 published studies were included in the final analysis and 2.) studies only reporting differences in disturbed and undisturbed landscapes (increase, decrease, varied, or no change) without published prevalence data (68 cases within 36 studies). Overall, we found that disturbed landscapes had higher pathogen prevalence. We reviewed potential indirect drivers (types of landscapes), direct drivers (features associated with landscapes), and mechanisms (changes in ecology caused by the indirect and direct drivers) that may account for the increase in pathogen prevalence between the landscapes. High pathogen prevalence in wildlife living in disturbed landscapes may serve as an indicator of the negative consequences of unsustainable human development. Having this understanding will enable wildlife managers to produce sustainable development solutions that will improve their predictions of infection and reduce prevalence of harmful pathogens in sensitive populations.
Keywords: human-disturbed; disease; wildlife